An Overview of Pharmaceutical Co-Crystal - Ancheria, Rahul Kumar; Jain, Saloni; Kumar, Deepak; Soni, Sankar Lal; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Pharmaceutical co-crystals are nonionic supramolecular complexes and supramolecular chemistry. Pharmaceutical co-crystal consists of active pharmaceutical ingredients and coformers. Pharmaceutical co-crystals can be employed to improve vital physicochemical characteristics of a drug, including solubility, dissolution, bioavailability and stability of pharmaceutical compounds while maintaining its therapeutic activity. Co-crystals can be constructed through several types of interaction, including hydrogen bonding, pi-stacking, and vander Waals forces. Pharmaceutical co-crystals could play a major role in the future of API formulation. Pharmaceutical co-crystal can be improvement future aspect problems related physicochemical properties of API